Hal-Hal yang Memengaruhi Keputusan Wakif untuk Berwakaf Uang di Kabupaten Purworejo - Meilinia Rositanti; Neneng Hasanah (Department of Islamic Economics, IPB University, 2022)
Cash waqf is a form of waqf innovation that is more flexible in management because it can be invested into the real and financial sectors. Cash waqf has an important role as a multiplier effect in the economy. Potential of cash waqf in Purworejo Districtis is very large. However, this potential has yet to be realized. The low accumulation of cash waqf that has not yet reached the potential is influenced by the community, especially waqif. Therefore, this study aims to analyze the factors affecting waqif’s decision to donate cash waqf at Purworejo District. Data collection is done by the questionnaires given to 60 waqif at Purworejo District. Descriptive analysis and logistic regression are used as research method in this study. The result shows that waqif’s decision to donate cash waqf is affected by their income and knowledge on cash waqf and the age of the waqif has a significant negative effect on the waqif's decision to cash waqf.